Peningkatan Pemahaman Narrative Text Mahasiswa Jurusan Sastra Daerah Dan Ilmu Perpustakaan Fakultas Ilmu Budaya Melalui Shrinking Strategy - Edward; Hutahaean, Sorta; Rizky, Ramanda (Journal of Social and Community Service, 2025)
This community service is "Improving Narrative Text Understanding of Students of Regional Literature and Library Science Department, Faculty of Cultural Sciences Through Shrinking Strategy". This IbM aims to provide knowledge and skills to students of Regional Literature Department, Faculty of Cultural Sciences, Lancang Kuning University. Language teaching, in this case, Reading Comprehension really needs to be considered and improved because in this era students will be more required to read articles or books in foreign languages. To understand English discourse, there are several strategies that can be done, one of which is 'Shrinking Strategy'. Through this strategy, it is hoped that students of Regional Literature and Library Science Department will find it easier to understand English discourse, especially narrative text types, so that the understanding process becomes more effective and efficient.